Pengaruh Metode Sosiodrama untuk Menumbuhkan Sikap Empati Siswa Kelas VII - Falah, Safa Zahroin Nazilatul; Widyarto, Wikan Galuh (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2023)
Empathy is the ability to put oneself in another person's position. Individuals who have an empathetic attitude will have a tendency to be able to place themselves in all social situations. Researchers used quantitative methods with a pre-experimental research approach using a One Group Pretest Posttest design on a population of 15 students at SMPN 1 Sumbergempol Tulungagung class VII C, while for data sampling using Purposive Sampling method with 15 students as research sample. The results of the research show that: 1) The level of empathy for class VII students at SMPN 1 Sumbergempol is 9 students in the very low category, 8 students in the low category, 8 students in the high category and 5 students in the very high category. 2) Based on the results of the paired samples test on the pre-test and post-test scores of students' empathy attitudes, there is a significant change, namely the significance value (2-tailed) 0.000 <0.05, which means that there is a significant difference between before and after being given guidance service treatment. sociodrama method group. 3) Then, the results of the N-Gain Score are worth 59, 59%. Based on these results, it can be concluded that H1 is accepted, namely the sociodrama method can foster an empathetic attitude in class VII students at SMPN 1 Sumbergempol Tulungagung.